Answer:
Given all the blanks true explained below.
Step-by-step explanation:
Given the pairs of triangle,
First pair, ΔABC and ΔUVW
In these triangles to prove triangles congruent we need all three sides equal but AB≠UV. Hence, not congruent
Second pair, ΔABC and ΔGHJ
To prove triangles congruent we need all three sides equal but AB≠GH Hence, not congruent
Third pair, ΔABC and ΔPQR
To prove triangles congruent we need all three sides equal
AB=PQ=2 units
[tex]BC=\sqrt{(-1+4)^{2} + (1-4)^{2} } =\sqrt{18}units[/tex]
[tex]QR=\sqrt{(-1-2)^{2} + (-1+4)^{2} } =\sqrt{18}units[/tex]
[tex]AC=\sqrt{(-1+4)^{2} + (1-2)^{2} } =\sqrt{10}units[/tex]
[tex]PR=\sqrt{(-1-2)^{2} + (-1+2)^{2} } =\sqrt{10}units[/tex]
Hence, BC=QR, AC=PR
All 3 sides equal. By SSS rule both triangles congruent.
Fourth pair, ΔGHJ and ΔUVW
GH=UV=3 units
HJ=VW=2 units
Hence, by Pythagoras theorem,
GJ=UW=[tex]\sqrt{3^{2}+2^{2}}=\sqrt{13} units[/tex]
Hence, All 3 sides equal. By SSS rule both triangles congruent.
Fifth pair, ΔGHJ and ΔPQR
To prove triangles congruent we need all three sides equal but PQ≠GH Hence, not congruent
Sixth pair, ΔPQR and ΔUVW
To prove triangles congruent we need all three sides equal but PQ≠UV. Hence, not congruent